A re-description of the eastern Pacific swellshark, Cephaloscyllium ventriosum (Garman 1880) (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with comments on the status of C. uter (Jordan & Gilbert 1896) - Silva, Jayna A. Schaaf-Da; Ebert, David A. (Zootaxa, 2008)
The genus Cephaloscyllium Gill 1862 (Chondrichthyes, Carcharhiniformes, Scyliorhinidae), arguably has one representative species in the eastern Pacific, C. ventriosum (Garman 1880). While the C. ventriosum holotype was collected from central Chile, a dubious species, C. uter, (Jordan & Gilbert 1896) was described from California. Garman (1913) classified C. uter as a junior synonym of C. ventriosum. This study marks the first morphometric and meristic analysis comparing the holotype of C. ventriosum from Chile with California Cephaloscyllium specimens and presents a revision of the genus for the eastern Pacific. Based on a comparison of morphometric and meristic data from specimens collected from Monterey, California; Santa Catalina Island, California; Santa Barbara, California; Guadalupe Island, Mexico; and Valparaiso, Chile, it is concluded that the California and Chilean Cephaloscyllium species represent a single, wide-ranging species, C. ventriosum.